Naskah Ilmu Segala Rahasia yang Ajaib Kontemplasi Tarekat Naqsyabandiyah dan Pembangunan Karakter - Nur Rahmah (Jurnal Lektur Keagamaan, 2012)
This text is composed by Syaikh Mai’un bin Khalifah Rajab, a Naqsyabandi sufi master from Pauh Duo Solok, West Sumatra. The text belongs to the member of the Naqsyabandi mystical order in Batu Bajarang. It deals with the teachings of the Naqsyabandi Khalidi order. It explicates the mystical concepts such as rabithah, dhikr ithm al-dhat, dhikr nafyi ithbat, dhikr al-lataif, the ethics of grave visit, the completion prayer, tawassul, and the latifah. These teachings are still relevant for the modern life